1991
DOI: 10.1016/0166-3542(91)90069-4
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic and therapeutic activities of 7-thia-8-oxoguanosine against Punta Toro virus infections in mice

Abstract: The biological response modifier 7-thia-8-oxoguanosine was evaluated in mice against the hepatotropic Adames strain of Punta Toro virus. When administered intraperitoneally in divided doses, significant protection from death was conferred at doses of 50 and 100 mg/kg/day given 24 and 17 h pre-virus inoculation, 25-100 mg/kg/day administered 4 h pre- and 3 h post-virus challenge, and 12.5 to 100 mg/kg/day administered 24 and 31 h after virus inoculation. These doses preventing death reduced liver icterus scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…This association indicates that isatoribine must induce an immune response to achieve an anti-HCV effect, consistent with preclinical data. [18][19][20][21] Although OAS and viral concentrations showed little or no change after a single dose of 800 mg isatoribine, these biological markers were substantially changed both immediately before and 24 hours after the 7th daily dose. Circulating neopterin and IP10 were elevated after 6 days of once-daily administration of 800 mg isatoribine, providing additional evidence of immunological activation that is consistent with a TLR7 agonist mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This association indicates that isatoribine must induce an immune response to achieve an anti-HCV effect, consistent with preclinical data. [18][19][20][21] Although OAS and viral concentrations showed little or no change after a single dose of 800 mg isatoribine, these biological markers were substantially changed both immediately before and 24 hours after the 7th daily dose. Circulating neopterin and IP10 were elevated after 6 days of once-daily administration of 800 mg isatoribine, providing additional evidence of immunological activation that is consistent with a TLR7 agonist mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…14 In preclinical studies, isatoribine does not exhibit direct antiviral activity or significant cytotoxicity in vitro; however, through stimulation of innate immunity, isatoribine does prevent or reverse otherwise lethal viral infections in various acute infection models in mice. [18][19][20][21] Based on this preclinical profile, and in view of the need for new anti-HCV therapies, we performed a clinical proof-of-concept study with isatoribine to determine whether treatment with a TLR7 agonist can achieve a demonstrable antiviral effect at a well-tolerated dose in patients chronically infected with HCV.…”
mentioning
confidence: 99%
“…Both agents induced a rapid (within 1 h of treatment) production of interferon. Recent work has shown that interferon induction is of major importance in the antiviral activity of TOGuo against Semliki Forest (16) and Punta Toro (17) virus infection in mice. In both models, antibody to alpha/beta interferon completely abrogated the protective effect of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…TOGuo has no in vitro antiviral activity against a large number of DNA and RNA viruses, however. The effects in animals are primarily due to interferon induction (16,17), although natural killer (NK) cells (6,16), lymphocytes (6), and macrophages (3,7) are also activated. The role of interferon in combating acute virus infections has been well documented (5,8), whereas activated cells of the immune system, although necessary in the overall fight against virus infections, seem to play a lesser role (1,21).…”
mentioning
confidence: 99%
“…The availability of these rodent models makes PTV a viable alternative to the use of Rift Valley fever virus for antiviral studies because the latter is highly restricted and requires high-level containment facilities. To that end, numerous evaluations of promising antivirals have been conducted using the PTV models of acute phlebovirus-induced disease (5)(6)(7)(8)(9)(10)(11)(12). Moreover, several large studies have involved the evaluation of immune modulators and have demonstrated that the PTV is acutely sensitive to IFN inducers (5,10).…”
Section: P Unta Toro Virus (Ptv)mentioning
confidence: 99%